Effect of heterogeneity of subjects of industrial irradiation processes on spatial distributions of absorbed doses upon electron beam, X-ray and gamma irradiation - Dyuldya, S.V.; Bratchenko, M.I. (Вопросы атомной науки и техники, 2007)
By means of Monte Carlo computer modeling the effects of heterogeneity and spatial arrangement of irradiated disposable syringes on the absorbed dose deposition profiles has been studied for different kinds of irradiation. Substantial deviations from the predictions of conventional approximation of homogenized medium have been found for electron beam irradiation. The dependencies of irradiation process parameters on the orientation and the regularity/stochasticity of the product loading pattern, the variations of dose accumulation in component parts of a syringe and the non-equilibrium dose effects on the internal surface of a syringe needle have been investigated.